Ketekunan Dalam Perlombaan Iman Kepada Yesus Kristus Berdasarkan Surat (Ibrani 12:1-3) - Lengis Nurlatu; Abad Jaya Zega (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The Book of Hebrews 12:1-3 provides profound guidance on the significance of perseverance in the journey of faith towards Jesus Christ. In this abstract, we will explore key concepts found in the text. Hebrews 12:1 urges us to cast off every hindrance and sin that impedes us, enabling us to run with perseverance in the race of faith. This reflects the importance of focusing on our relationship with Jesus Christ and letting go of anything that obstructs spiritual growth. The concept of perseverance is emphasized in Hebrews 12:1, depicting the journey of faith as a race requiring endurance, resilience, and strong focus. Perseverance is necessary because this journey is not a short sprint but a long-term marathon that demands enduring commitment. Hebrews 12:2 directs our focus to Jesus as the pioneer and perfecter of our faith. Our perseverance is not a result of our efforts alone but is strengthened by fixing our gaze on Jesus Christ. This reflects that true perseverance involves a deep understanding of Christ's presence and glory. Hebrews 12:3 reminds us to endure suffering without losing heart, following the example of Him who endured suffering. Perseverance is required in facing challenges and hardships, and a steadfast focus on Jesus Christ motivates us to endure in the midst of trials. In conclusion, Hebrews 12:1-3 provides a strong foundation for understanding the role of perseverance in our journey of faith towards Jesus Christ. By shedding burdens, focusing on Christ, and facing suffering with perseverance, we can navigate the race of faith with determination and attain the eternal reward prepared for those who remain faithful.